Analysis Of Extremely Low Frequency (ELF) Magnetic Field Exposure Impact On The Mass Of Great Red Chili Plant (Capsicum annum.L) - Karina Laksmiari; sudarti sudarti (JURNAL PEMBELAJARAN FISIKA, 2021)
The Extremely Low Frequency (ELF) magnetic field is a component of the electromagnetic wave spectrum with a frequency of <300 Hz. This research is an experimental study with the aim of examining the effect of exposure to Extremely Low Frequency (ELF) magnetic fields on the mass of chili plants (Capsicum annum L). Data collection techniques used are direct measurements. The results showed that chilli seeds exposed to a 300µT ELF magnetic field for 30 minutes gave a fresher and drier mass than the other samples. The use of a 30-minute duration ELF 300µT magnetic field on chili seeds gave better results for fresh and dry mass of chili plants.